Enhancement of Solubility and Dissolution Rate of Poorly Soluble Anticancer Drug Using Nanostructured Lipid Carrier Based Drug Delivery System - Sabale, Vidya; Jiwankar, Manasi; Sabale, Prafulla (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Prostate cancer is the leading cause of death in men over the age of 50, making it one of the most common cancers. Current treatments available such as chemotherapy, surgery are associated with many side-effects. Due to non-specificity and poor solubility of many anticancer drugs, less amount of drug is available at the absorption site. The current study aimed to develop Nanostructured Lipid Carriers (NLCs) of the poorly soluble anticancer drug Flutamide. Materials and Methods Flutamide-loaded Nanostructured Lipid Carriers (NLCs) containing biocompatible lipids Precirol ATO 5 (Solid lipid), flaxseed oil (Liquid lipid) and surfactants were synthesized using the melt emulsification ultrasonication method. Koliphor RH40 and Tween 80 were used in combination in 1:1 ratio. Results The interaction of drug and excipients was investigated using Fourier Transform Infrared (FTIR). Phase transition of Flutamide was confirmed using differential scanning calorimetry during the processing of NLCs. Solubility Flutamide increased significantly when it was prepared in the form of NLCs. Flutamide-loaded NLCs were found to be eighteen times more soluble in distilled water than the pure drug. Flutamide loaded NLCs were five times, three times, and four times more soluble in pH 1.2, 6.8, and 7.4 PBS than the pure drug. Conclusion According to the findings, Flutamide can be formulated into nanostructured lipid carriers with improved solubility.
Keywords: Flutamide; Solubility; Nanostructured lipid carriers; Lipids